"An Extra Variable to Consider"—Vaccine-Induced Seropositivity and Adolescent HIV Vaccine Clinical Trials. Issue 5 (9th February 2022) - Fatola, Omolayo; Corneli, Amy; Perry, Brian; Hanlen-Rosado, Emily; Nsonwu, Adora; Constantine, Evangelia P; Thompson, Amelia B
Abstract: Our study explores the understanding of vaccine-induced seropositivity (VISP) and its potential impact on US adolescents' and caregivers' willingness to participate in adolescent HIV vaccine clinical trials. Findings from in-depth interviews suggest that addressing concerns about VISP will be essential for future pediatric HIV vaccine trials in the United States. Abstract : Addressing adolescents' and their caregivers' concerns about vaccine-induced seropositivity will likely be essential to the success of future pediatric HIV vaccine trials in the United States.